การชักนำให้เกิดการกลายในต้นแพงพวยโดยการฉายรังสีแกมมาแบบเฉียบพลัน - ผดุงศิลป์, ณัฏฐา; เตชะศีลพิทักษ์, ธัญญะ; วงศ์ชาวจันท์, เฌอมาลย์; จันจุฬา, ณัฐพงค์ (Thai Journal of Science and Technology, 2015)
บทคัดย่อ การศึกษาผลของการฉายรังสีแกมมาแบบเฉียบพลันต่อการกลายพันธุ์ของต้นแพงพวย Catharanthus roseus L. พันธุ์ Mediterranean Deep Rose โดยฉายรังสีที่ปริมาณ 0, 50, 100, 150 และ 200 เกรย์ กับเมล็ดก่อนออกปลูกมีการรอดชีวิตของต้นหลังฉายรังสี 30 วัน สูงกว่า 50 เปอร์เซ็นต์ ทุกสิ่งทดลอง ปริมาณรังสีที่ระดับ 50-200 เกรย์ ทำให้กลีบดอกแพงพวยมีลักษณะรอยด่างขาวกระจายอยู่ทั่วกลีบดอก ปริมาณรังสีที่ 50 และ 100 เกรย์ ทำให้บางดอกมีจำนวนกลีบดอกลดลงเหลือ 4 กลีบ ปริมาณรังสีที่ 150 และ 200 เกรย์ พบลักษณะใบบิดเบี้ยวและใบ 2 แฉก ในระยะต้นกล้า ปริมาณรังสีที่ 50 เกรย์ ทำให้ต้นแพงพวยมีขนาดทรงพุ่มกว้างที่สุดและออกดอกเร็วกว่าปกติ ส่วนปริมาณรังสีที่ 200 เกรย์ ทำให้ดอกแพงพวยมีขนาดใหญ่ที่สุด คำสำคัญ : การรอดชีวิต; ดอกด่าง; ใบบิดเบี้ยว; ความเสียหายทางสรีรวิทยา Abstract The effect of acute gamma irradiation on mutation of Catharanthus roseus cv. Mediterranean Deep Rose was studied. The seeds were irradiated with gamma ray at the dose of 0, 50, 100, 150 and 200 gray. The results showed that the survival percentages of at 30 days after irradiation were higher than 50 in all treatments. Gamma radiation doses of 50, 100, 150 and 200 gray resulted in blemish petal colour. Some flowers had four petals after irradiation with 50 and 100 gray. The treated plants at the dose of 150 and 200 gray showed curl and two lobe leaves at the seedling stage. The 50 gray treated plants had the greatest plant width and the earliest flowering days while the 200 gray treated one had the largest flower size. Keywords: survival percentage; white blemish; curl leaf; physiological damage